2015
DOI: 10.1007/s10853-015-9041-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural stability and grain growth kinetics in an extruded fine-grained Mg–Gd–Y–Zr alloy

Abstract: The grain growth kinetics of an extruded finegrained Mg-9Gd-4Y-0.4Zr (wt%) alloy was investigated by static annealing in the temperature range of 673-773 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…SEM micrographs of the alloy at r = 1.5 mm are shown in Fig 5 . Also, it should be mentioned that, in accordance with an earlier study [30], the EDS results confirm the presence of some small Zr-rich precipitates in the microstructure of the alloy.…”
Section: Microstructural Evolution During Hpt Processingsupporting
confidence: 90%
See 1 more Smart Citation
“…SEM micrographs of the alloy at r = 1.5 mm are shown in Fig 5 . Also, it should be mentioned that, in accordance with an earlier study [30], the EDS results confirm the presence of some small Zr-rich precipitates in the microstructure of the alloy.…”
Section: Microstructural Evolution During Hpt Processingsupporting
confidence: 90%
“…In the initial extruded condition prior to HPT, the material displayed a fairly equiaxed and uniform grain structure with an average grain size of ~8.6 m: a detailed microstructural characterization of the extruded condition was given earlier [30]. SEM micrographs of the alloy at r = 1.5 mm are shown in Fig 5 .…”
Section: Microstructural Evolution During Hpt Processingmentioning
confidence: 99%
“…Accordingly, attempts have been made to improve their thermal stability through the addition of different alloying elements. It was reported that the addition of gadolinium (Gd) and other rare earth (RE) elements can lead to a remarkable improvement in the thermal stability of microstructure and mechanical properties at high temperatures due to solution hardening and precipitation strengthening [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are reports that rareearth (RE) elements can greatly improve the microstructural stability of Mg alloys at high temperatures [1][2][3][4]. Among the newly-developed Mg-RE based alloys are Mg-Gd-Y alloys which exhibit superior strength [5][6][7] and creep resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These exceptional properties originate primarily from the influence of RE elements on the restoration processes and the textural evolution of Mg alloys at elevated temperatures [14,15] and also from the presence of RE-rich precipitates having superior thermal stability [4]. These results suggest that it would be valuable to investigate the hot deformation of Mg-Gd-Y alloys to obtain a better understanding of the dominant flow mechanisms at these high temperatures.…”
Section: Introductionmentioning
confidence: 99%